Effect of light intensity on the photosynthesis and stomatal density of selected plant species of Gunung Ledang, Johor - Aisha Idris,; Alona Cuevas Linatoc,; Mohd Fadzelly Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Light intensity influences the photosynthesis and stomatal density in plants. In this study, it was hypothesized that if the transpiration rate of a plant is low, then the stomatal density might be high. The objective of this research is to investigate the effect of varying light intensity on the photosynthetic capacity and stomatal density of Mikania micrantha, Tridax procumbens, Clidemia hirta and Centella asiatica plant species of Gunung Ledang, Johor, Malaysia. Sun-exposed and shaded species were selected for the study. Gas exchange characteristics including stomatal conductance to water vapour (gsw), transpiration rate and intracellular CO2 (Ci) were measured using LI-6400 portable photosynthesis system while net assimilation rate (Anet), light saturation point (LSP), light compensation point (LCP), and apparent quantum yield (Aqy) were calculated from the photosynthetic light response curve. Stomatal density was determined using nail polish impression method and examined using a stereo microscope. The result of this study shows that high light intensity influences the net assimilation rate and stomatal density of the studied plants. As the light intensity increases, Amax, LSP, LCP and stomatal density of the plants increases. There is a significant difference between the light response characteristics and stomatal density of the sun-exposed and shaded species (P < 0.05). A statistically significant negative correlation (P < 0.05) was achieved among stomatal density and transpiration rate. As stomatal density increases, the transpiration rate decreases. The result leads to a conclusion that Mikania micrantha can efficiently utilise the amount of light available more than Tridax procumbens, Clidemia hirta and Centella asiatica and grow abundantly as dominant species in an introduced environment.